Association of dyslipidemia with intakes of fruit and vegetables and the body fat content of adults clinically selected for a lifestyle modification program - Takahashi, Mauro Massao [UNESP]; de Oliveira, Erick Prado [UNESP]; Moreto, Fernando [UNESP]; Mclellan, Katia Cristina Portero [UNESP]; Burini, Roberto Carlos [UNESP] (Archivos Latinoamericanos Nutricion, 2010)
To investigate the relationship of dyslipidemia with demographic distribution and patterns of body fat and dietary intakes. From a universe of adults clinically selected for a lifestyle modification program 979 subjects (409 males and 570 females, 52.2 +/- 9.6 years) fulfilled the inclusion criteria. Overnight-fasting plasma was assayed (dry chemistry) for triglycerides (TG), total (TC) and HDL fraction of cholesterol given the non-HDL (n-HDL) fraction by the difference. Anthropometric assessment included body weight (kg), height (m), fat (bioelectrical impedance) and waist circumference (WC). Food intake was assessed by the 24-hour recall questionnaire and the food groups evaluated through recommendations from an adapted food pyramid. The chances of dyslipidemia from other variable changes were determined by logistic regression with p < 0.05. Normal values of BMI and WC were protective against all dyslipidemia markers whereas only hypercholesterolemia was influenced by diet (meat intake > 2 servings). Dietary intakes have protective effects against hypertriglyceridemia with whole grains, odds ratio (OR) 0.342 (Cl 95%, 0.154-0.760), fruits >= 3 servings (OR 0.523, 0.290-0.941) and vegetables >= 4 servings (OR 0.360, 0.176-0.735). In general total body and abdominal adiposity influenced all dystipidemia markers while dietary intake of fruits and vegetables protected against triglyceridemia.

Investigar las relaciones de dislipidemia con distribución demográfica y patrones de masa corporal e ingestión de alimentos. De un universo de adultos clínicamente seleccionados para un programa de modificación de estilo de vida, 979 sujetos (409 hombres y 570 mujeres, 52,2 ± 9,6 años) cumplieron con los criterios de inclusión. Se examinó el plasma cosechado tras ayuno nocturno (química seca) para averiguar si hay la presencia de triglicéridos (TG), colesterol total (CT) y fracción de colesterol dada la fracción no HDL por diferencia. Una evaluación antropométrica incluyó peso corporal (kg), altura (m), grasa (impedancia bioeléctrica) y circunferencia de la cintura (CC). Se evaluó la ingestión de alimentos con el cuestionario de tipo recordatorio de 24 horas y los grupos de alimentos evaluados por la pirámide de alimentos recomendada. Se determinaron las probabilidades de dislipidemia de otros cambios variables con regresión logística p<0,05. Valores normales de BMI y CC protegieron de todos los marcadores dislipidémicos mientras solamente hipercolesterolemia fue influenciada por la dieta (ingestión de carne >2 porciones). El consumo en la dieta protege de hipertrigliceridemia con odds ratio de granos integrales (OR) 0,342 (CI 95%, 0,154-0,760), frutas >3 porciones (OR 0.523, 0.290-0.941) y hortalizas >4 porciones (OR 0.360, 0.176-0.735). En general la adiposidad corporal total y abdominal influenció todos los marcadores de dislipidemia y solamente la trigliceridemia fue protegida por ingestión de frutas y hortalizas en la dieta.
Associación de la dislipidemia con la ingestión de frutas y vegetales y el contenido de grasa corporal de adultos seleccionados para un programa de modificación del estilo de vida
Keywords: Dyslipidemia; body composition; dietary components